Non-viral Microbial Keratitis in a Tertiary Care Hospital in Bangladesh - Reza, Mohammed Selim; Chowdhury, Shamsul Alam; Talukder, Paritush Kanti; Islam, Md Tabibul; Hossain, Md Altaf; Hussain, Nizam Jamil; Jhuma, Azima Aktar (Medicine Today, 2021)
Introduction: Microbial keratitis is a serious ocular infectious disease that can lead to significant visual loss and ophthalmic morbidity. Objectives were to see the profile of non-viral microbial keratitis in a tertiary care hospital in Bangladesh. Materials and Methods: This cross-sectional study was conducted in the Department of Ophthalmology, Sylhet MAG Osmani Medical College Hospital, Sylhet between January 2015 and December 2016. Results: The mean age of the patients was 46.7 ± 16.5 years with male preponderance (54.4%). The most common predisposing factors were trauma (66.7%), and chronic dacryocystitis (25.6%). Fungal growth was more frequent compared to bacterial growth 70 (77.7%) versus 30 (33.3%), p<0.01). Gram positive organisms were Staphylococcus epidermidis (11.1%), Staphylococcus aureus (3.3%); gram negative organisms were Pseudomonas aeruginosa (12.2%), Klebsiella species (3.3%) and Escherichia coli (3.3%). Aspergillus species (71.4%) was the commonest fungus. Others were Penicillium species (7.1%), Fusarium species (8.6%), Mucor (10.0%) and Rhizopus (2.9%). Conclusion: Fungi are more frequent cause of non-viral keratitis. Watering, redness, pain or burning sensation, corneal opacity and dimness of vision are clinical profiles of non-viral microbial keratitis. Medicine Today 2021 Vol.33(2): 133-137